Using real-world data in pediatric clinical trials: Lessons learned and future applications in studies of persistent pulmonary hypertension of the newborn. Issue 4 (August 2022) - Miller, Thomas F.; Kaiser, Andreas; Schmelter, Thomas; Lippert, Joerg; Davis, Jonathan M.
Abstract: Persistent pulmonary hypertension of the newborn (PPHN) is a complication of term birth, characterized by persistent hypoxemia secondary to failure of normal postnatal reduction in pulmonary vascular resistance, with potential for short- and long-term morbidity and mortality. The primary pharmacologic goal for this condition is reduction of the neonate's elevated pulmonary vascular resistance with inhaled nitric oxide, the only approved treatment option. Various adjunctive, unapproved therapeutics have been trialed with mixed results, likely related to challenges with recruiting the full, intended patient population into clinical studies. Recently, real-world data and subsequent derived evidence have been utilized to improve the efficiency of various pediatric clinical trials. We aim to provide recent perspectives regarding the use of real-world data in the planning and execution of pediatric clinical trials and how this may facilitate more streamlined assessment of future therapeutics for the treatment of PPHN and other neonatal conditions.